Efficacy of Alendronate and Cholecalciferol Combination in the Treatment of Osteoporosis in Patients with Chronic Viral Hepatitis Receiving Antiviral Therapy: Report of Two Cases - İlke Coşkun Benlidayı; Zainb Al-Bayati; Rengin Güzel (Galenos Yayinevi, 2015)
In this case report, the efficacy of 12-month alendronate and cholecalciferol combination therapy for the treatment of osteoporosis in two male patients with chronic viral hepatitis aged above 60 years who were on antiviral treatment was evaluated. The patients were diagnosed with osteoporosis via dual energy x-ray absorptiometry while receiving 245 mg tenofovir disoproxil fumarate once daily and started on alendronate and cholecalciferol combination (70 mg/2800 IU). Baseline T-scores of the two patients were -2.6 and -4.9, respectively. Baseline bone mineral density (BMD) and 25(OH)D (ng/ml) values were compared with post-treatment values. Regarding the first case, following treatment, lumbar, femoral neck and total hip BMD values were improved by 1.9%, 5.2% and 13.8%, respectively. In the second case, L1-L4 lumbar, femoral neck and total hip BMD values were improved by 23.2%, 25.9% and 14.8%, respectively. However, when pre- and posttreatment 25(OH)D levels were compared, a decrease was observed in both patients. In conclusion, 12-month treatment with alendronate and cholecalciferol combination improved BMD values, in patients with chronic viral hepatitis who were on antiviral therapy. Considering that tenofovir therapy effects vitamin D metabolism independently in these patients, it is necessary to control 25(OH)D levels in a regular basis and to support the patient with adequate vitamin D supplementation, in order to optimize serum vitamin D levels and prevent from vitamin D insufficiency. (Turkish Journal of Osteoporosis 2015;21: 96-9)